Mapping the digital humanities landscape: A bibliometric review of research and emerging frontiers - Abang Mohd Razif Abang Muis; Musmuliadi Kamaruding; Mohd Sohaimi Esa; Abg Mohd Shukri Abg Muis (The Elite Scientific Forum, Pakistan, 2025)
traditional humanities research. This study presents a comprehensive bibliometric analysis of digital humanities scholarship, utilizing data from the Scopus database to map research trends, identify key contributors, and uncover emerging thematic areas. A total of 550 original research articles published between 2001 and 2024 were analysed using bibliometric indicators, citation metrics, and network analysis techniques. The findings reveal a steady increase in digital humanities publications, with significant contributions from the United States, the United Kingdom, and China. Key research themes include digital heritage preservation, artificial intelligence applications, and big data analytics, indicating an increasing interdisciplinary convergence. Furthermore, co-occurrence analysis highlights dominant research clusters, emphasizing digital archiving, cultural heritage, and computational methodologies. This study underscores the growing significance of digital humanities in cultural preservation, knowledge dissemination, and technological advancements. The results provide valuable insights for researchers, policymakers, and institutions aiming to foster innovation and collaboration in the evolving landscape of digital humanities.